2012
DOI: 10.1177/000313481207800530
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multiple Wire Localization in Breast Conservation

Abstract: Variability exists regarding the surgical technique in breast conservation therapy. The purpose of this project was to determine differences between single (SH) or flanking (FH) hooked needle localization wires used for nonpalpable breast lesions. We retrospectively reviewed 201 female patients at a single institution from 2004 to 2008. All patients had biopsy-proven ductal carcinoma in situ or invasive disease. Comparisons were made in regard to margin status, reoperation, completion mastectomy, size of lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…However, we did find that bracketing was the localization modality most likely to correlate with incomplete resection and residual disease. This has been demonstrated elsewhere . This finding supports the use of bracketing in tumors with attributes known to place patients at risk for positive margins: diffuse, multifocal, and large size tumors.…”
Section: Discussionsupporting
confidence: 83%
“…However, we did find that bracketing was the localization modality most likely to correlate with incomplete resection and residual disease. This has been demonstrated elsewhere . This finding supports the use of bracketing in tumors with attributes known to place patients at risk for positive margins: diffuse, multifocal, and large size tumors.…”
Section: Discussionsupporting
confidence: 83%
“…Fillion et al, who compared 79 patients treated with BWL to 122 patients treated with WGL, reported more positive margins (39% vs. 18%; P ¼ .039) and re-excisions (44% vs. 25%; P ¼ .004) for BWL. 28 Tumor size in their BWL group (2.9 cm) was larger than in WGL (1.5 cm) (P < .001). This might explain the higher rate of tumor positive margins in BWL as tumor size larger than 2 cm is associated with involved margins.…”
Section: Discussionmentioning
confidence: 86%
“…This might explain the rate of tumor negative resection margins of BWL in this study (77%) being on the high range compared with those of other studies, which range between 44% and 83%. 24,25,[27][28][29] Another explanation for the high rate of negative margins in this study is the use of preoperative magnetic resonance imaging in almost all (82%) patients to get an adequate estimation of the true tumor extent. Fillion et al, who compared 79 patients treated with BWL to 122 patients treated with WGL, reported more positive margins (39% vs. 18%; P ¼ .039) and re-excisions (44% vs. 25%; P ¼ .004) for BWL.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This technique was developed and popularized in the 1970s, and continues to be broadly utilized. With the validation of breast conserving therapy (BCT) for cancer, WL with multiple wires, placed in a bracketed fashion around the lesion of interest, facilitates targeted excision of expansive lesions . Despite its utility, WL has been shown to have several technical disadvantages.…”
Section: Introductionmentioning
confidence: 99%